Law and war - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Stanford, California : Stanford University Press, 2014)
This work explores the cultural, historical, spatial, and theoretical dimensions of the relationship between law and war - a connection that has long vexed the jurisprudential imagination. Law has emerged as a force that stands over and above war, endowed with the power to authorise and restrain, to declare and limit, to justify and condemn.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: War (International law); Jurisprudence; Law; Jurisprudence & general issues; Methods, theory & philosophy of law; International law